Research Status of the Grindability of Steel Slag - Yan Su; Shuxian Liu; Pingan Xu; Yimiao Nie; Ling Wang (Kuangchan zonghe liyong, 2022)
The steel slag, which is called overburned Portland cement clinker, is a kind of metallurgical waste which is difficult to be grinded because it contains some refractory substances such as calcium ferrite and forsterite. The grinding performance is related to the various functions of steel slag as cement additive. In this paper, the influence of the chemical composition and mineral composition of steel slag on the grindability is reviewed, and the methods of improving the grindability of steel slag, such as the modification of steel slag, the addition of grinding aids and composite grinding, are introduced. Aiming at the problem of poor grindability of steel slag, the process control in the formation process of steel slag is put forward, the special grinding aids for steel slag are developed according to the mineral composition of steel slag, the classification treatment and the composite mixing with slag and fly ash are put forward Measures such as grinding are taken to improve the grindability and gelling activity of steel slag.